2012
DOI: 10.1016/j.ijpddr.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of chloroquine resistance in Plasmodium – Is the redox system involved?

Abstract: Chloroquine (CQ) was once a very effective antimalarial drug that, at its peak, was consumed in the hundreds of millions of doses per year. The drug acts against the Plasmodium parasite during the asexual intraerythrocytic phase of its lifecycle. Unfortunately, clinical resistance to this drug is now widespread. Questions remain about precisely how CQ kills malaria parasites, and by what means some CQ-resistant (CQR) parasites can withstand much higher concentrations of the drug than others that also fall in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 105 publications
(185 reference statements)
1
32
0
Order By: Relevance
“…2) 5 . Malaria parasites avoid heme toxicity by converting dimers of hematin into inert crystals (called hemozoin) and perhaps also by heme degradation through peroxidative or glutathione-mediated pathways 6 . Drugs that interfere with crystal formation have been some of the most successful in malaria therapy.…”
Section: The Digestive Vacuole and Continuing Drug Discoverymentioning
confidence: 99%
“…2) 5 . Malaria parasites avoid heme toxicity by converting dimers of hematin into inert crystals (called hemozoin) and perhaps also by heme degradation through peroxidative or glutathione-mediated pathways 6 . Drugs that interfere with crystal formation have been some of the most successful in malaria therapy.…”
Section: The Digestive Vacuole and Continuing Drug Discoverymentioning
confidence: 99%
“…For vivax malaria, chloroquine, a drug that also induces oxidative stress (18), was abandoned in 2012 and replaced by dihydroartemisinin plus piperaquine. This change was based on data from clinical therapeutic efficacy studies (day 28 follow-up, PCR-uncorrected WHO protocol) that showed proportions of treatment failure ranging from 0% to 17.4% (in Ratanak Kiri province, 2010) following a chloroquine regimen, while in the same areas, dihydroartemisinin plus piperaquine was 100% effective (19).…”
mentioning
confidence: 99%
“…Plasmodia manage this toxicity by converting hematin into hemozoin and heme degradation through peroxide or glutathione-mediated pathways [12]. CQ prevents the detoxification of heme in the parasite's food vacuole.…”
Section: Mode Of Action/resistancementioning
confidence: 99%